FERTILIZATION AS A STRATEGY FOR MITIGATION AND ADAPTATION OF CORN CULTURE FOR FUTURE CLIMATE CHANGES - Jaime-Huaman, Emerson (2021)
A modeling equation was carried out for climate changes in 2080 and 2099 under the fourth climate scenario proposed by the IPCC (Intergovernmental Panel on Climate Change) where a very high level of greenhouse gas emissions is assumed (RCP “Representative Concentration Pathway” 8.5); to predict the yield of corn production with low or no fertilization and high fertilization as a technique for adaptation and mitigation of the adverse effects of climate change. The percentage reduction in corn yield by 2080 with low or no fertilizer application is 30 to 55%, and with high fertilizer application it is 10 to 20%. Climate change would have negative impacts on future agricultural production and food security. Fertilization is one of the mitigation and adaptation strategies for corn cultivation in the face of climate change.